The Influence of Leverage and Independent Commissioners on Tax Avoidance with Firm Size as a Moderating Variable - Anggraeni, Silvia Ayu; Badjuri, Achmad (Manunggal Halim Jaya, 2025)
This study examines the effect of leverage and independent commissioners on tax avoidance with firm size as a moderating variable in 42 manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative approach was employed using multiple linear regression and moderated regression analysis (MRA). The results show that leverage has a significant positive effect on tax avoidance (β = 11.038, p < 0.001), while independent commissioners have a negative but insignificant effect (β = –2.990, p = 0.231). Firm size strengthens the leverage–tax avoidance relationship and weakens the independent commissioners-tax avoidance relationship, although both effects are statistically insignificant (p > 0.05). The regression model explains 35.6% of the variation in tax avoidance (Adjusted R² = 0.356, F = 8.570, p < 0.001). These findings contribute to agency theory and provide practical implications for policymakers and corporate managers in strengthening governance and tax compliance in Indonesia.